POLA TRANSFORMASI PELAKU EKONOMI DI ERA TRANSISI PANDEMIK KE NEW NORMAL - Muh. Arafah (Jurnal Ilmiah Al-Tsarwah : ilmu ekonomi dan keuangan (konvensional dan syariah), 2020)
This paper focuses on analyzing the changes in behavior carried out by three economic actors, from the government, business actors and consumers in the era of the pandemic transition to the new normal. This paper includes a literature study that draws data from reading results in the form of books, journals and other readings. Based on existing searches, the results obtained show that the government sector issued policies to save the country's economy while still following the health protocol. From the business sector, business actors use technology in the form of social media to market and sell their products. Meanwhile, the consumer sector uses cellphone application services to order daily necessities to avoid the spread of Covid-19 by staying at home.